(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the frequency of evidence-based practice (EBP) utilization and identify factors associated with EBP application among physicians in the Outpatient Department of Le Van Thinh Hospital. Methods: A cross-sectional study was conducted among all physicians working in the department (N=160). Data were collected using a self-administered questionnaire with high internal consistency (Cronbach’s alpha > 0.88). EBP utilization was measured based on the frequency of performing the five steps of the EBP process. Associated factors were examined using a multivariable logistic regression model with variable selection based on AIC. Results: The proportion of physicians with high EBP utilization was 45.63%, while 54.38% demonstrated low utilization. The regression model identified two statistically significant predictors: part-time physicians were substantially less likely to practice EBP (OR = 0.12; p = 0.022), and higher personal barriers were inversely associated with EBP utilization (OR = 0.32; p = 0.024). Conclusion: Although EBP has been integrated into clinical practice, its implementation remains inconsistent and not yet routine. EBP utilization is influenced more by personal barriers and organizational integration than by demographic characteristics. Interventions should simultaneously strengthen physicians’ EBP competencies and enhance workplace support systems, with particular attention to part-time physicians.